Ökonomische Anmerkungen zur aktuellen Netzneutralitätspolitik in den USA - Nadine Neute; Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2016)
– Following the FCC Notice of proposed Rulemaking and the request for public comments a lively debate on how to protect the open Internet ensued and has now been closed by the approval of strong net neutrality rules by the FCC. This paper discusses the economic merit of alternative forms of regulation and points out implications of the current rules for further proceedings. We particularly highlight the parallels between the European and the American legal contexts and discuss un-der which circumstances prioritization influences the likelihood of market failure. From the (non)available empirical evidence on attempts to foreclose downstream markets and from the fact that interference with the freedom of opinion has been dealt with swiftly we conclude that the former legal framework was sufficient to deal with those concerns, while the new framework has severe drawbacks. Although a binding formalization of prioritization rules is necessary to reduce uncertainty and to close a debate which has been going on now since 2003 it will not pacify the ongoing debate, as H.R.2666 - No Rate Regulation of Broadband Internet Access Act has passed the House of Representatives and might counteract the FCCs net neutrality priciples.
Keywords: L86; L82; L40; K21; D80; 330; Netzneutralität; Internetökonomie; Medienökonomik; Wettbewerb